2011
DOI: 10.1261/rna.2399411
|View full text |Cite
|
Sign up to set email alerts
|

Potent and systematic RNAi mediated silencing with single oligonucleotide compounds

Abstract: RNA interference (RNAi) has been established as an important tool for functional genomics studies and has great promise as a therapeutic intervention for human diseases. In mammalian cells, RNAi is conventionally induced by 19-27-bp RNA duplexes generated by hybridization of two complementary oligonucleotide strands (oligos). Here we describe a novel class of RNAi molecules composed of a single 25-28-nucleotide (nt) oligo. The oligo has a 16-nt mRNA targeting region, followed by an additional 8-10 nt to enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…AMOs are synthetic oligonucleotides with reverse complementary sequences to mature miRNAs that can tightly bind to their miRNA targets with high specificity as well as optimal stability and pharmacokinetics necessary to block miRNA function. Since naked RNA is rapidly degraded in the blood stream secondary to significant nuclease enzymatic degradation [Czauderna et al 2003], AMOs are chemically modified to confer nuclease stability, increase binding affinity, as well as facilitate entrance into the cell and miRNA-induced silencing complex [Lapierre et al 2011]. These oligonucleotide chemical modifications may include nucleotide modifications to the phosphate backbone and/or sugar or use of nonribose backbones [Lennox and Behlke, 2011].…”
Section: Mirnas As Therapy In Ibd: Design and Delivery Of Mirna Agentsmentioning
confidence: 99%
“…AMOs are synthetic oligonucleotides with reverse complementary sequences to mature miRNAs that can tightly bind to their miRNA targets with high specificity as well as optimal stability and pharmacokinetics necessary to block miRNA function. Since naked RNA is rapidly degraded in the blood stream secondary to significant nuclease enzymatic degradation [Czauderna et al 2003], AMOs are chemically modified to confer nuclease stability, increase binding affinity, as well as facilitate entrance into the cell and miRNA-induced silencing complex [Lapierre et al 2011]. These oligonucleotide chemical modifications may include nucleotide modifications to the phosphate backbone and/or sugar or use of nonribose backbones [Lennox and Behlke, 2011].…”
Section: Mirnas As Therapy In Ibd: Design and Delivery Of Mirna Agentsmentioning
confidence: 99%
“…Synthetic small interfering RNAs (siRNAs) have been widely used to transiently knockdown gene expression in cultured cells for loss of function (LoF) analyses. In mammalian cell models it has been shown that allele-specific silencing of disease genes with siRNA can be achieved by targeting either a linked single-nucleotide polymorphism (SNP) or the disease mutation directly (Lapierre et al, 2011). For a polyglutamine neurodegenerative disorder, the SNP was employed to design a siRNA able to silence the mutant Machado-Joseph disease/ spinocerebellar ataxia type 3 allele while sparing expression of the WT allele (Miller et al, 2003).…”
Section: Therapeutic Targeting Of Rnamentioning
confidence: 99%
“…For example, including two 2′- O -Me-RNA nucleotides at the 5′-end of the siRNA reduces its ability to enter the miRNA pathway [117,119]. siRNA designs that ensure loading of the correct guide strand into RISC can also help to reduce off-target effects [120126]. …”
Section: Control Experiments: You Can Never Have Too Manymentioning
confidence: 99%